Mewujudkan Kesetaraan Gender dalam Upaya Pencegahan Stunting pada Anak: Studi Kasus pada PKH Kapanewon Jetis, Yogyakarta - Laras Nurul Hidayati; Zulkipli Lessy (KOLONI, 2023)
Stunting is a condition of impaired growth in a child caused by inadequate nutritional intake during the childhood. This can have negative impacts on the physical, cognitive, and social development of the child. Some fathers often neglect their role and responsibility to fulfill the needs of their child such as nutrition and care. The child development therefore is important to be observed in order to provide his or her future and achive their optimum growth. This research emphasizes the need for gender equality due to the absence of the fathers to take care of the child. Furthermore, fathers need to actively participate in the child care and share roles with mothers. By doing so, stunting can be prevented early and optimal child development can be supported. The research method used in this study is descriptive narrative. The aim of this research is to emphasize the importance of father involvement in nutritional responsibility and child care, as well as promote gender equality in efforts to prevent stunting. The results show that a balanced family involvement in caregiving roles can overcome stunting and create an environment that supports child growth.